Students social and emotional intelligence development based on eco-humanistic pattern - Sergeyeva, Tetyana Viktorivna; Turlakova, Natalya Borysivna; Nazymko, Olena Viktorivna (Potere della ragione Editore, 2021)
The article is devoted to the problem of students’ social and emotional intelligence formation in the course of personal efficiency development. Interactive training activity is based on eco-humanistic technology aimed at students’ conscious self-development. It is proposed five-stage circle that modals real conditions of self-development in everydayness. Students are considered as efficient agents of positive changes who are motivated in developing their professional and social environment as a condition of their cognitive and personal development. The whole process is based on the psychological patterns of human-environment interdevelopment.
Keywords: social intelligence; emotional intelligence; self-development; eco-humanistic technology; personal efficiency; human-environment interdevelopment